Inhibitory mechanism of tangeretin, a citrus flavone on the sphingosylphosphorylcholine (SPC)-induced vascular smooth muscle contraction - Nan Li; Ying Zhang; Tomoka Morita; Hiroko Kishi; Sei Kobayashi (Elsevier, 2022)
We previously discovered that the SPC/Fyn/Rho-kinase (ROK) pathway mediates the Ca2+-sensitization of coronary arterial smooth muscle (CASM) contraction leading to vasospasm, a major cause of sudden death. Lately, we have been trying to find and develop more natural edible compounds which can treat and/or prevent the SPC-induced abnormal CASM contraction, and finally the first to discover that tangeretin (5,6,7,8,4'-pentamethoxyflavone), a natural compound extracted from citrus plants, can inhibit the SPC-induced CASM contraction both in the pretreatment and posttreatment. In porcine CASM tissues, tangeretin showed remarkable inhibitory effects on the SPC-induced contraction with modest inhibitory effects on the high K+-depolarization-induced Ca2+-dependent contraction, both in pretreatment and posttreatment at the optimal concentrations; Regarding the mechanisms, tangeretin markedly abolished the SPC-induced cell contraction through inhibiting the SPC-induced activation and translocation of Fyn and ROK from the cytoplasm to the cell membrane in cultured CASM cells, resulting in the reduction of phosphorylation of myosin light chain. Taken together, these findings indicate that tangeretin, upon pre- or post-treatment, inhibits the SPC-induced CASM contraction through suppressing the Fyn/ROK signaling pathway, thereby suggesting that tangeretin can be a potential candidate for the treatment and/or prevention of vasospasm.